Conservación neoliberal de la naturaleza en la Patagonia chilena: explorando nuevas modalidades ecoextractivistas y tensiones hidrosociales - Esteban Ortiz Robles; Robinson Torres Salinas; Alejandro Salazar-Burrows; Fabien Bourlon (Revista de Estudios Sociales)
Chilean Patagonia, a historically remote region known for its vast natural landscapes of global ecological importance, has a rich environmental history of resistance, epitomized by the monumental Patagonia Without Dams movement, which fiercely opposed transnational hydroelectric projects. While traditional extractivism continues to face strong opposition, capital has shifted towards “green” adaptations, manifesting as eco-extractive practices that commodify nature. This article seeks to identify and analyze these emerging eco-extractive threats. Drawing from a Latin American political ecology perspective and employing a relational, multi-method approach—ethnographic, discourse, and documentary analysis—the study examines hydro-social reconfigurations and the eco-extractive dynamics of tourism development and land parceling in Puerto Río Tranquilo and the Valle Exploradores in the Aysén region of Chile. The findings reveal that ecotourism and the proliferation of “eco-lot” real estate projects for conservation purposes are refined forms of eco-extraction, driven by the neoliberal conservation paradigm. This paradigm reimagines Patagonia as a tourist haven and a territory for real estate-driven conservation, creating hydro-social tensions by reshaping perceptions of water availability and quality. It also imposes neoliberal conservation narratives that overshadow and subsume traditional territorialities and cultural meanings. The critique advanced in this article challenges the “green” facade of these conservation projects, arguing that they represent not genuine ecological awareness but rather a form of real estate speculation reliant on green rhetoric to legitimize and expand their scope.